2014
DOI: 10.1007/s12199-014-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

The genotype of the transporter associated with antigen processing gene affects susceptibility to colorectal cancer in Japanese

Abstract: The genotype of the TAP1 gene is associated with susceptibility to CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…And polymorphisms in TAP genes [21][22][23][24][25] To date, several studies have reported the association between polymorphisms in TAP genes and human cancers. [26][27][28][29][30] For example, Ozbas-Gerceker et al found rs1057141 and rs2228396 to be associated with haematological malignancies, and Einstein et al detected an association between rs1057141 and rs1135216 and CC in an American population. 31 However, the association data of TAP polymorphisms with CC in Chinese population was rare, especially cervical intraepithelial neoplasia (CIN).…”
Section: Introductionmentioning
confidence: 99%
“…And polymorphisms in TAP genes [21][22][23][24][25] To date, several studies have reported the association between polymorphisms in TAP genes and human cancers. [26][27][28][29][30] For example, Ozbas-Gerceker et al found rs1057141 and rs2228396 to be associated with haematological malignancies, and Einstein et al detected an association between rs1057141 and rs1135216 and CC in an American population. 31 However, the association data of TAP polymorphisms with CC in Chinese population was rare, especially cervical intraepithelial neoplasia (CIN).…”
Section: Introductionmentioning
confidence: 99%
“…1 Immune evasion, developed by tumor cells to survive attack by immune responses, is one of the plausible mechanisms underlying carcinogenesis. 2 The transporter associated with antigen processing (TAP) protein plays a critical role in the processing and presentation of intracellular antigens. 3 Cellular proteins including tumor associated gene products are degraded predominantly through the ubiquitin-proteasome pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, a study reported that the annual number of cancer diagnoses will increase from 14 to 22 million by 2032 . Immune evasion, developed by tumor cells to survive attack by immune responses, is one of the plausible mechanisms underlying carcinogenesis …”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood lymphocytes using the conventional method [30]. Detection of single nucleotide polymorphisms (SNPs) of PER3 (rs2640908) was performed using the restriction fragment length polymorphism (PCR-RFLP) technique.…”
Section: Polymerase Chain Reaction (Pcr) Amplification and Genotypingmentioning
confidence: 99%